View of the pillar of the antarala - Temples of India Project Team (Jio Institute, 2024)
The pillars of the antarala have a square base. The middle square shaft is carved with the half lotus medallion. Above this medallion, the shaft turns circular, topped with an amalaka, and a plain square abacus.